Early in patient post-operative rehabilitation of right anterior cruciate ligament reconstruction using semitendinosus and gracilis graft in Kabaddi player: A case study (Indian Journal of Case Reports, 2026)
The anterior cruciate ligament (ACL) is a primary stabilizing structure of the knee joint, resisting anterior translation and rotational movement of the tibia relative to the femur. Injuries to the ACL represent one of the most significant knee injuries encountered in young, athletically active individuals, causing immediate functional impairment and long-term sequelae, such as instability, meniscal damage, and early osteoarthritis if inadequately managed. A 17-year-old male Kabaddi player underwent ACL reconstruction using a semitendinosus and gracilis tendon autograft. Post-operative physiotherapy commenced on the 2nd day following a structured protocol aimed at early recovery and graft protection. During the first 2 weeks, rehabilitation emphasized pain and edema control through cryotherapy and elevation, gradual progression of passive knee flexion and extension within a pain-free range, and isometric strengthening of the quadriceps, hamstrings, hip abductors, and gluteal muscles. Active ankle pumps were included to maintain circulation, and the patient was trained in partial weight-bearing ambulation with crutches under physiotherapist supervision. After 2 weeks of structured rehabilitation, the patient demonstrated significant improvement in knee mobility, swelling, pain, muscle activation and extension lag. Knee flexion reached 100°, with full extension and partial weight bearing was achieved with minimum assistance.